Lateral hypothalamus hypocretin/orexin glucose-inhibited neurons promote food seeking after calorie restriction - Suraj B. Teegala; Pallabi Sarkar; Dashiel M. Siegel; Zhenyu Sheng; Lihong Hao; Nicholas T. Bello; Luis De Lecea; Kevin D. Beck; Vanessa H. Routh (Elsevier, 2023)
Objective: The present study tests the hypothesis that changes in the glucose sensitivity of lateral hypothalamus (LH) hypocretin/orexin glucose-inhibited (GI) neurons following weight loss leads to glutamate plasticity on ventral tegmental area (VTA) dopamine neurons and drives food seeking behavior. Methods: C57BL/6J mice were calorie restricted to a 15% body weight loss and maintained at that body weight for 1 week. The glucose sensitivity of LH hypocretin/orexin GI and VTA dopamine neurons was measured using whole cell patch clamp recordings in brain slices. Food seeking behavior was assessed using conditioned place preference (CPP). Results: 1-week maintenance of calorie restricted 15% body weight loss reduced glucose inhibition of hypocretin/orexin GI neurons resulting in increased neuronal activation with reduced glycemia. The effect of decreased glucose on hypocretin/orexin GI neuronal activation was blocked by pertussis toxin (inhibitor of G-protein coupled receptor subunit Gαi/o) and Rp-cAMP (inhibitor of protein kinase A, PKA). This suggests that glucose sensitivity is mediated by the Gαi/o-adenylyl cyclase-cAMP-PKA signaling pathway. The excitatory effect of the hunger hormone, ghrelin, on hcrt/ox neurons was also blocked by Rp-cAMP suggesting that hormonal signals of metabolic status may converge on the glucose sensing pathway. Food restriction and weight loss increased glutamate synaptic strength (indexed by increased AMPA/NMDA receptor current ratio) on VTA dopamine neurons and the motivation to seek food (indexed by CPP). Chemogenetic inhibition of hypocretin/orexin neurons during caloric restriction and weight loss prevented these changes in glutamate plasticity and food seeking behavior. Conclusions: We hypothesize that this change in the glucose sensitivity of hypocretin/orexin GI neurons may drive, in part, food seeking behavior following caloric restriction.